1998
DOI: 10.1159/000054358
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Activation of Pituitary-Adrenal Axis in Healthy Young and Elderly Subjects during Somatostatin Infusion

Abstract: In this study we explored, in man, the effect of acute attenuation of growth hormone (GH) release induced by somatostatin (SRIH) on ACTH and cortisol plasma levels. Sixteen young (8 women, aged 23–32 years, and 8 men, aged 18–27 years) and 14 elderly (8 women, aged 65–82 years, and 6 men, aged 65–70 years) healthy subjects volunteered to participate in this investigation. Each subject was tested on two separate occasions by: (1) a 90-min i.v. infusion of SRIH given in 50 ml 0.9% saline delivered at a rate of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Human corticotroph seem to respond differently to SST and its analogs, since SST infusion in healthy adults may result in an activation of the HPA axis, suggesting that changes in HPA axis might be mediated acutely by SSTinduced reduction in GH plasma levels and complex interplay at central level [45]. Other studies, however, demonstrated that SST or octreotide administration do not influence ACTH secretion in normal healthy individuals [46,47], but can repress ACTH secretion in patients with adrenal insufficiency [48] and in patients with Nelson's syndrome [49].…”
Section: Somatostatin Analogsmentioning
confidence: 99%
“…Human corticotroph seem to respond differently to SST and its analogs, since SST infusion in healthy adults may result in an activation of the HPA axis, suggesting that changes in HPA axis might be mediated acutely by SSTinduced reduction in GH plasma levels and complex interplay at central level [45]. Other studies, however, demonstrated that SST or octreotide administration do not influence ACTH secretion in normal healthy individuals [46,47], but can repress ACTH secretion in patients with adrenal insufficiency [48] and in patients with Nelson's syndrome [49].…”
Section: Somatostatin Analogsmentioning
confidence: 99%